The effectiveness of Nicotiana tabacum leaf extract as antibacterial agent against Aggregatibacter actinomycetemcomitans: an experimental study - Vinsensius, Theresa Christy; Widyastuti, Wiena (Padjadjaran Journal of Dentistry, 2025)
Introduction: Dental caries is often associated with bacterial pathogens such as Aggregatibacter actinomycetemcomitans, which lower the oral pH and contribute to tooth damage. Calcium hydroxide (Ca(OH)2) is commonly used in vital pulp therapy due to its antibacterial properties; however, it may cause adverse effects, including pulp necrosis. As a natural alternative, tobacco leaf extract (Nicotiana tabacum) extract has shown potential due to its content of antibacterial compounds such as flavonoids and terpenoids. This study aims to analyse the antibacterial effect of Nicotiana tabacum leaf as an antibacterial agent against A. actinomycetemomitans. Methods: An in-vitro experimental laboratory research with a post-test-only control group design. The antibacterial activity was tested using the plate count method on samples from seven different groups. The test was conducted using the microdilution method in 96-well plates, followed by the plate count method for bacterial enumeration. The test samples included Nicotiana tabacum leaf extract at concentrations of 3.125%, 6.25%, 12,5%, 25%, and 50%, with calcium hydroxide serving as the positive control and distilled water as the negative control. The data were analysed using one-way ANOVA followed by Tukey’ HSD post hoc test. Results: The minimum inhibitory concentration (MIC) of the extract against Aggregatibacter actinomycetemcomitans of 12.5% while a concentration of 25% represented the minimum bactericidal concentration (MBC). The 25% concentration exhibited antibacterial activity comparable to that of calcium hydroxide. The Tukey HSD post hoc test revealed significant differences between the negative control and the Nicotiana tabacum leaf extract at concentrations of 6.25% (p=0.025), 12.5% (p=0.001), 25% (p=0.001), and 50% (p=0.001). This study aims to analyse the antibacterial effect of Nicotiana tabacum leaf as an antibacterial agent against A. actinomycetemomitans. Conclusion: Nicotiana tabacum leaf extract exhibits antibacterial activity against Aggregatibacter actinomycetemcomitans, with an MIC of 12.5% and an MBC of 25%.